A case of inappropriate sexual behaviour in mixed dementia. Issue 4 (July 2014) - Gomes‐Pinto, Alister
<x xml:space="preserve">Abstract</x> There is currently no first‐line psychotropic indicated in the management of inappropriate sexual behaviours in dementia (ISBD). This case report highlights the treatment of a patient with mixed dementia, who developed significant ISBD symptoms which resolved upon commencing a popular SSRI. The authors include an evidence‐based summary of other medications which have demonstrated some success in reducing ISBDs.